2020
DOI: 10.1590/1809-4430-eng.agric.v40n3p352-355/2020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Operational Conditions of Mechanized Harvesting on Sugarcane Losses and Impurities

Abstract: Operational conditions of mechanized harvesting can affect the quality of harvested sugarcane. Therefore, the aim of this study was to assess the influence of the displacement speed and cutting height on the quality of the raw material during the mechanized harvest of sugarcane. Vegetable losses were accounted for in the field by manual collection of the fractions left after harvest. Vegetable and mineral impurities were determined at the processing stage in the laboratory. Both the displacement speed and cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, increasing the speed can affect the cutting tools' performance. Martins and Ruiz [11], evaluating raw material losses in sugarcane crops, found no differences for this parameter as a function of operational speed. Marques Filho et al [13] showed that harvest speed could increase raw material losses.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, increasing the speed can affect the cutting tools' performance. Martins and Ruiz [11], evaluating raw material losses in sugarcane crops, found no differences for this parameter as a function of operational speed. Marques Filho et al [13] showed that harvest speed could increase raw material losses.…”
Section: Resultsmentioning
confidence: 92%
“…The base cutter is a vital sugarcane harvester component. Its work efficiency was directly related to production cost per unit area and its decisive impact on sugarcane yield in the following year [10][11][12]. During mechanized harvesting, the stalk's sugarcane base is cut by two rotating disks equipped with cutting knives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the mechanical harvester operates smoothly and adheres to specifications, it noticeably decreases the levels of mud, stone, and cane root (Xie et al, 2018). Mechanical removal methods, such as vibration, can often be used to screen out the sand, gravel, and soil (Martins and Ruiz, 2020). However, the top, leaf and cane root are unavoidable impurities as they are naturally part of each sugarcane stem (de Mello et al, 2022).…”
Section: Introductionmentioning
confidence: 99%